Forming Students' Independent Character through Scouting Extracurricular Activities at SDN 2 Kertanegara, Purbalingga - Permatasari, Dhina; Wakhudin, Wakhudin (Journal of English Language and Education, 2025)
This study aims to describe the formation of independent character in elementary school students. In practice, student independence is often hampered by overprotective parenting patterns and high levels of independence. This study attempts to solve the problem of independent character formation through Scouting extracurricular activities in Grade IV of SDN 2 Kertanegara, Purbalingga, involving 22 students as participants. This study uses a qualitative-descriptive approach with a phenomenological method. Data were obtained using observation, interviews, and documentation studies. The results show that activity planning, structured implementation, and evaluation through reflection and General Competency Requirements (SKU) provide a significant contribution to increasing student independence, especially in terms of responsibility, discipline, and cooperation. In conclusion, scouting activities systematically shape independent character, but the success of the program is influenced by collaboration between teachers as mentors, and a supportive school environment.